THE EFFECT OF ACADEMIC SUPERVISION AND TRAINING ON THE IMPLEMENTATION OF TEACHER PROFESSIONALISM AND ITS IMPLICATIONS ON ELEMENTARY SCHOOL TEACHERS' PERFORMANCE IN PULOSARI DISTRICT - Irnawati, Irnawati; Rustandi, Tata; Permana, Angrian (International Journal of Economy, Education and Entrepreneurship (IJE3), 2025)
This research is motivated by findings that indicate the low effectiveness of academic supervision, limited training, low teacher professionalism, and less than optimal teacher performance in elementary schools. These problems were identified through primary and secondary data obtained from the research location. The main objective of this study is to examine the influence of academic supervision and training on teacher professionalism, and to examine how these factors impact teacher performance improvement. The study was conducted at a public elementary school in Pulosari District, Pandeglang Regency. The study population involved 203 teachers with a sample of 135 respondents. The method used was a quantitative approach with a Likert-scale questionnaire instrument, while data analysis was conducted using Smart PLS regression. The results of the study indicate that academic supervision and training have a positive and significant effect on teacher professionalism. Furthermore, teacher professionalism plays a significant role as a mediating variable, strengthening the influence of academic supervision and training on teacher performance. In other words, the better the academic supervision and training provided, the higher the level of teacher professionalism, which ultimately impacts performance improvement. The conclusion of this study confirms that improving the quality of academic supervision, training, and teacher professionalism is a strategic factor in optimizing the performance of educators in elementary schools.